Use of social networks in the marketing of information services in the university libraries: A field study in the libraries of universities in the east of Algeria. - benghida, wissam; benharir, nadjat (Journal of Social Sciences and Humanities, 2021)
This research paper seeks to identify the extent of the use of university libraries located in the eastern Algeria of its pages available through social networks as a virtual space to display and market various information services provided to its users, and to reveal the nature of the marketing activities used and know the feasibility and interaction of users with them. The field survey method was used to suit the nature of the study. The results revealed that six university libraries have Facebook and Twitter pages, which are used in the electronic marketing of information services (marketing information sources, library marketing, marketing library services) in order to attract The maximum number of users from inside and outside the university. The results of the study also revealed the weak interaction of users with the marketing activities mentioned above for the university libraries under study. Résumé Cet article cherche à identifier l'étendue de l'utilisation des bibliothèques universitaires situées dans l'est de l'Algérie vers ses pages disponibles via les réseaux sociaux en tant qu'espace virtuel pour afficher et commercialiser divers services d'information fournis à ses bénéficiaires, et révéler la nature des activités de marketing utilisées et connaitre la faisabilité et l'interaction des bénéficiaires avec eux. La méthode d'enquête sur le terrain a été utilisée en fonction de la nature de l'étude. Les résultats ont révélé la possession de six bibliothèques universitaires de pages sur Facebook et Twitter, qui sont utilisées dans le marketing électronique des services d'information (sources d'information marketing, marketing de bibliothèque, services de bibliothèque marketing)afin d’attirer le plus grand nombre possible de bénéficiaires à l'intérieur et à l'extérieur de l'université. Les résultats de l'étude ont également révélé la faible interaction des bénéficiaires avec les activités de marketing mentionnées ci-dessus pour les bibliothèques universitaires étudiées.